Implementation of an Emergency Medical Card and a Continuity of Care - Olola, C. H. O.; Rowan, B.; Narus, S.; Smith, M.; Hastings, T.; Poynton, M.; Nebeker, J.; Hales, J.; Evans, R. S. (Methods of Information in Medicine, 2009)
Objectives: To describe the design and implementation procedures for an emergency medical card (EMC) and a continuity of care (CoC) report using the continuity of care record (CCR) standard. We also describe studies to evaluate the effectiveness of these documents in Co C.Methods: We convened weekly planning, design, development, implementation, and evaluation meetings, involving 25 outpatient clinics at Intermountain Healthcare. The CCR standard schema and documentation from American Society for Testing and Materials were used to develop the data model. An outside consultant provided further advice on committee-approved designs. We then developed a functional design document for the CCR application implementation. Healthcare professionals (medical doctors and physician assistants) and fourth-year medical students will simulate the will simulate the EMC and CoC report use and assess their usefulness in Co C. The reviewers will review three randomly selected patient cases, using patient information in the electronic medical record, EMC and CoC report. A structured questionnaire with Likert scale will assess the reviewers’ perceptions of the documents’ usefulness in medical decision making. Other studies will compare patient- and HCP-entered data to evaluate the effect of patient-entered data on the quality of HCP-entered data and assess user-satisfaction with the documents’ usefulness in Co C.Results: An automated CCR application compliant with the CCR standard was developed and integrated in an already implemented patient portal at the Intermountain Healthcare clinics. Patients use the application to view, add, modify their information and use the data plus EMR data to create EMC and CoC report.Conclusions: The CCR standard can be used to implement an application to enable patients to not only view but add or modify personal health records, and create, print and share paper EMC and CoC report with HCPs. The documents can be created using HCP-maintained EMR data, in addition to patient-entered data as is currently the norm.
Keywords: Continuity of care record standard; continuity of care; continuity of patient care; emergency medical card; electronic medical record